Lossless compression for transmitting 'ECG in SMS' with high quality for mobile telecardiology systems. (2017) - Diana, M.; Deisy, C.
This paper presents a novel lossless compression for 'ECG in SMS' (LCES) deployable on resource-constrained devices like mobile phones for efficient use in remote health monitoring systems. Even losslessly compressed ECG suffers transmission loss in GSM networks due to use of special character set stated by the GSM standards. The LCES overcomes these challenges by adopting the ETSI GSM 03.38 character set in the symbol substitution phase to abstain loss in ECG transmission. The LCES was implemented and tested as an Android App using MIT-BIH Arrhythmia and Compression Test Databases. An average compression-ratio of 7.03 and percentage-root-mean-square-distortion as low as 0.022 proving superior compression performance and quality for real-time mobile-based remote health monitoring systems were obtained.